Shortboard performance surfing: A qualitative assessment of maneuvers and a sample periodized strength and conditioning program in and out of the water - Everline, C. (Strength and Conditioning Journal, 2007)
Surfing can be defined as a risk sport due to several variables including but not limited to currents, wave force, water aspiration, and collisions with equipment, rocks, coral reefs, and other surfers. It is essential for surfers, both novice and elite, to have a significant base of paddling strength, balance, and general physical fitness in order to meet the demands of an unpredictable oceanic environment and to prevent repetitive motion injuries. The purpose of this paper is to describe the physiological demands of surfing and to introduce a periodized strength and general fitness model.